Curriculum making in Europe : policy and practice within and across diverse contexts - Priestley, Mark (Mark R.) (Emerald Group, 2021)
In the context of profound social, political and technological changes, recent global trends in education have included the emergence of new forms of curriculum policy. Addressing a gap in the literature, this book investigates the ways in which curriculum policy is influenced, formulated, and enacted in a number of countries-cases in Europe.